Comparison of sexual dysfunction between diabetic and non-diabetic women - Narges Shams Alizadeh; Modabber Arasteh; Behzad Mohsenpour; Farzaneh Karimian; Nasim Shams Alizadeh (Wolters Kluwer Medknow Publications, 2013)
Context: Sexual dysfunction (SD) among diabetic women is an important disorder. It has many negative effects on general health. Aims: This study aimed to compare SD status between diabetic and non-diabetic women. Settings and Design: This study was conducted on 200 women, half of them diabetic and the others as non-diabetic in Tohid Hospital (Sanandaj, Iran). Materials and Methods: The non-diabetic group was matched for age (±5 years) and education. Data were collected using an interview-based questionnaire containing demographic characteristics and female sexual function index (FSFI). Statistical Analysis Used : Univariate and multivariate analyses were performed to assess and interpret the results. Results: Analyses of the data showed that low educational levels, longer duration of diabetes and poor controlled diabetes were associated with the lower FSFI scores. In both groups the prevalence of SDs for all FSFI domains was high. Furthermore, multivariate analysis showed that these three variables were associated with lower FSFI scores. Conclusions: Study confirms that Kurdish Iranian diabetic women are at an increased risk of SD. Low educational level, longer duration of diabetes, and poor controlled diabetes were associated with a lower FSFI score.